What determines the mean reversion speed of NAV spreads?. Issue 4 (2nd October 2022) - Schiller, Alexander; Woltering, René-Ojas; Weis, Christian; Sebastian, Steffen
ABSTRACT: In this paper, we study the mean reversion behaviour of NAV spreads for a global sample of 219 listed real estate stocks. We find NAV spreads for companies trading at a high discount to mean revert fastest. Remarkably, we also provide evidence that online search attention impacts the mean reversion speed of NAV spreads: Stocks with lower levels of online search attention mean-revert significantly faster than those with higher levels. Our global research setting allows us to show that a country's average NAV spread has an impact on the NAV spreads of individual stocks. Ultimately, we find that the NAV spread of companies receiving high levels of online search attention has a disproportionately high impact on the NAV spreads of other companies.